A Picture of Job Insecurity Facing British Men. - Nickell, S; Jones, P; Quintini, G (2002)
This paper considers three aspects of the job insecurity facing British men in the last two decades. The probability of becoming unemployed, the costs of unemployment in terms of real wage losses and the probability that the continuously employed will experience substantial real wage losses. The first of these has not risen in the last two decades, the second has risen by around 40% and the third has risen, particularly for the top skill groups.